Crecimiento de cultivares de acelga (Beta vulgaris var. cicla) bajo diferentes dosis de fertilización orgánica - Villalba, Franco Ramiro (2024)
n the province of Misiones, one of the main challenges is to increase local production of fresh vegetables for consumption, as 80% of the demand is supplied from outside the region. One of the primary difficulties in developing local horticulture is the lack of information regarding the ecophysiological behavior of cultivars in subtropical conditions. At the same time, the use of organic fertilizers is common; however, there is a lack of information regarding their proper management to meet the nutrient demands of the horticultural crops. This study aims to evaluate the influence of different doses of organic fertilizer on the growth, physiological parameters, and yield of two swiss chard cultivars (Beta vulgaris var. cicla) in two contrasting seasons in northeastern Argentina. For this purpose, a 4 x 2 bifactorial experiment was conducted in a completely randomized block design with four replications. Four doses of organic fertilizer were evaluated, determined to provide 0, 50, 100, and 150 kg N ha-1, and the swiss chard cultivars "Penca Blancas" and "Penca Verde" were used. To evaluate the growth of swiss chard in contrasting seasons, two independent trials were conducted, in the spring-summer season (November and December 2022) and in the autumn-winter season (between May and July 2023). Crop dry matter, relative and absolute growth rates, net assimilation rate, and plant accumulation of nitrogen, phosphorus, potassium, calcium, and magnesium were measured. No effect of the applied fertilizer doses was found on the analyzed growth variables in either of the two growing seasons. In general terms, the plants accumulated more dry matter and showed higher growth rates in the spring-summer trial than in the autumn-winter trial. The Penca Verde variety stood out for being earlier and presenting a higher growth rate at the beginning of the crop cycle.